Pengaruh Likuiditas, Solvabilitas, dan Efektivitas Modal Kerja terhadap Profitabilitas Perusahaan Sub Sektor Farmasi yang Terdaftar di Bursa Efek Indonesia: (Periode 2017 – 2021) - Putri, Meisa; Friska, Della; Suharti; Purwanto, Dedik; H., Ardia R.; Pajriyanti, Vivi (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2024)
This study aims to analyze the effect of toxic liquidity with the Current Ratio, Solvency with the Debt to Equity Ratio, Effectiveness of Working Capital with Working Capital Turnover on Profitability in Pharmaceutical Sub Sector Companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The approach used in this research is a quantitative approach. The population in this study are pharmaceutical companies listed on the Indonesia Stock Exchange for the 2017-2021 period which totals 36 companies. The analysis technique used is multiple regression analysis, t test, F test, and the coefficient of determination using SPSS version 25 as an aid in calculations. The results of this study indicate that Liquidity has a positive and significant effect on Profitability with a significant p-value of 0,001 (<0,005). Solvability has a negative and significant effect on Profitability with a significant p-value of 0,001 (<0,05. The effectiveness of Working Capital has a positive and insignificant effect on Profitability with a significant p-value of 0,927 (> 0,05). significant to Profitability.The results of the R Square analysis of 0,707, this indicates Liquidity, Solvability and Effectiveness of Working Capital jointly affect Profitability of 70,7% and the remaining 29,3% is explained by other variables not analyzed in this study. Keywords: liquidity, solvability, the effectiveness of working capital, and profitability